The Effectiveness of Blended Synchronous and Asynchronous Learning for Teaching Reading Comprehension - Mukminatus Zuhriyah; Maskhurin Fajarina (AL-ISHLAH: Jurnal Pendidikan, 2022)
Some studies investigated the use of synchronous and asynchronous learning in EFL classrooms. However, the investigation of blended synchronous and asynchronous learning use in the reading comprehension class was scarce. Therefore, the researchers in this present study focused on investigating the effectiveness of the blended synchronous and asynchronous learning implementation for teaching reading comprehension. This study aimed to know whether or not there was a significant difference in the students’ reading comprehension ability before and after the blended synchronous and asynchronous learning implementation. This was a pre-experimental study with a one-group pretest-posttest design. Meanwhile, the population in this study were three classes of the third-semester students of non-English departments of a university in Jombang. One class consisting of twenty-five students was taken as the sample using purposive sampling. The experimental students were given a pretest of reading comprehension before getting the six-meeting treatment of blended synchronous and asynchronous learning. After the treatment finished, they did the reading comprehension posttest. After all the reading scores were collected, the descriptive statistics, normality test, and paired sample t-test were applied using SPSS. The t-test result showed that the obtained t-count (11.616) was higher than the t-table (2.063). That result revealed that the students’ reading comprehension ability was significantly different before and after the blended synchronous and asynchronous learning application. Thus, blended synchronous and asynchronous learning was effective for teaching reading comprehension. Then, it is highly recommended for EFL lecturers to combine synchronous and asynchronous learning in their remote English classes.